2010
DOI: 10.1002/cb.335
|View full text |Cite
|
Sign up to set email alerts
|

Proscription and its impact on anti‐consumption behaviour and attitudes: the case of plastic bags

Abstract: This paper empirically examines whether proscription of a habitual consumption item can act as a mechanism to develop anti-consumption behaviour and attitudes. The paper tracks a legislated retail ban on single-use polyethylene plastic bags, analysing 1167 interviews with shoppers before the ban's announcement, during a 4-month phasing-out period (and demarketing campaign), and when the ban was in full effect. Two hundred and fifty three interviews are repeated with the same individuals to allow identification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 27 publications
4
56
1
3
Order By: Relevance
“…He, 2010; Sharp et al, 2010) that can be affected by undesired factors as social desirability or a misperception about one's own behavior. On the other hand, studies that used objective measures typically only measured behavior on an aggregate level (i.e., number of plastic bags divided by retail sales index adjusted for inflation; Hasson et al, 2007), so there is no information about the effects of incentives on individual performance.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…He, 2010; Sharp et al, 2010) that can be affected by undesired factors as social desirability or a misperception about one's own behavior. On the other hand, studies that used objective measures typically only measured behavior on an aggregate level (i.e., number of plastic bags divided by retail sales index adjusted for inflation; Hasson et al, 2007), so there is no information about the effects of incentives on individual performance.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…On the other hand, studies that used objective measures typically only measured behavior on an aggregate level (i.e., number of plastic bags divided by retail sales index adjusted for inflation; Hasson et al, 2007), so there is no information about the effects of incentives on individual performance. Also, many studies evaluated the effectiveness of pricing policies by comparing plastic bag use before and after the implementation of the charge but without including adequate control groups Hasson et al, 2007;Sharp et al, 2010). Therefore, we cannot be completely sure whether effects are caused by the implementation of the charge, or to another factor not taken into account and thus not under control of the researcher.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…The packaging sector is responsible for the greatest utilisation of plastics, which corresponds to more than a third of the Brazilian consumption [1] . The plastic bags provided by markets, which are resistant and convenient, represent a large portion of all the plastic bags produced and supplied to consumers [2] . These data show the inherent need for the development of alternatives for the substitution, or at least the partial substitution, of this type of packaging with another material that is ecologically favourable and that exhibits properties similar to those of synthetic plastics.…”
Section: Introductionmentioning
confidence: 99%
“…Single-use plastic bags have become ubiquitous and the environmental impact of their disposal is well documented (Sharp et al, 2010). James and Grant (2003) and Lewis, Verghese and Fitzpatrick (2010) found that polymer-based 'bags for life' have lower environmental impacts than all types of singleuse bags.…”
Section: Introductionmentioning
confidence: 99%